Redefining the pharmacology and pharmacy subject category in the journal citation reports using medical subject headings (MeSH) - Minguet, Fernando; Salgado, Teresa M.; Santopadre, Claudio; Fernandez-Llimos, Fernando (International journal of clinical pharmacy, 2017)
Background The Journal Citation Reports (JCR) Pharmacology and Pharmacy subject category is heterogeneous. The inclusion of journals with basic and clinical scopes, which have different citation patterns, compromises comparability of impact factors among journals within the category. Objective To subdivide the Pharmacology and Pharmacy category into basic pharmacology, clinical pharmacology, and pharmacy based on the analyses of Medical Subject Headings (MeSH) as a proxy of journals’ scopes. Setting JCR. Method All articles, and respective MeSH, published in 2013, 2014, and 2015 in all journals included in the 2014 JCR Pharmacology and Pharmacy category were retrieved from PubMed. Several models using a combination of the 14 MeSH categories and specific MeSH tree branches were tested using hierarchical cluster analysis. Main outcome measure Distribution of journals across the subcategories of the JCR Pharmacology and Pharmacy subject category. Results A total of 107,847 articles from 214 journals were included. Nine different models combining the MeSH categories M (Persons) and N (Health Care) with specific MeSH tree branches (selected ad-hoc) and Pharmacy-specific MeSH (identified in previous research) consistently grouped 142 journals (66.4%) in homogeneous groups reflecting their basic and clinical pharmacology, and pharmacy scopes. Ultimately, journals were clustered into: 150 in basic pharmacology, 43 in clinical pharmacology, 16 in basic pharmacology and clinical pharmacology, and 5 in pharmacy. Conclusion The reformulation of the Pharmacology and Pharmacy category into three categories was demonstrated by the consistent results obtained from testing nine different clustering models using the MeSH terms assigned to their articles.